PSYCHOLOGICAL PORTRAIT AS A MEANS OF DEPICTION THE PSYCHE OF THE HERO IN THE PSYCHOLOGICAL NOVEL HERZOG BY SAUL BELLOW (Journal of Pharmaceutical Negative Results, 2022)
This article is devoted to the interpretation of the author's deep penetration into the inner world of the hero, a detailed description of the spiritual world of the character, the expression of emotional experiences with the help of a psychological portrait, which is one of the direct visual tools of "artistic psychology".In the psychodynamic portrait type, the image of the hero is characterized not by a detailed image, but by details specific to his appearance and mental state, which changes depending on the requirements of the situation, in the description of events and dialogues.